Laron syndrome - from man to mouse lessons from clinical and experimental experience - Laron, Zvi.; Kopchick, J. (Heidelberg Springer Berlin, 2010)
Laron syndrome (LS), or primary growth hormone (GH) insensitivity, was first described in 1966. Since then, many patients worldwide have been diagnosed with LS, which involves defects in the GH receptor that cause combined congenital deficiency of GH and IGF-I activities. In this comprehensive book the authors draw upon 50 years of multidisciplinary clinical and investigative follow-up of the large Israeli cohort of LS patients. The genetic basis of the syndrome is fully considered, and all aspects of the pathophysiology of IGF-I deficiency are described. Data derived from the recently generat.
Adjustment and rehabilitation problems of children, adolescents, and adults with Laron syndrome -- Laron syndrome patients with congenital IGF-I deficiency seem protected from malignant diseases -- Lifespan and mortality of patients with Laron syndrome -- IGF-I treatment of patients with Laron syndrome -- IGF-I stimulation of head growth in patients with Laron syndrome -- Effects of long-term administration of IGF-I on the adipose tissue and carbohydrate metabolism in children with Laron syndrome -- Comparison of the growth promoting response of IGF-I in children with Laron syndrome with that of hGH in children with isolated GH deficiency -- IGF-I treatment of adult patients with Laron syndrome -- Adverse effects encountered during IGF-I treatment of patients with Laron syndrome -- Summary of the clinical history: the Laron syndrome clock -- The Laron mouse -- Role of GH/IGF-I deficiency in aging -- Body composition, adipose tissue, and energy balance -- Metabolism and metabolic regulation -- Skeletal muscle -- Cardiac function in GHR-/-mice -- Bone -- GHR knockout and the CNS -- Cancer -- Reproduction -- Conclusions and future studies.
Electronic reproduction.
Keywords: Laron dwarfism; Laron dwarfism -- Treatment; Phenotype